Policy implementation of local governments in waste management in Dili City, Timor Leste - Leonio Maria Da Silva; Nursalam; Hendrik Toda (Journal of Governance and Accountability Studies, 2021)
Purpose: The purpose of this research is to analyze Policy Implementation of Local Government In Waste Management (Distrito) Dili City, Timor Leste. Research Methodology: The research method used in this research is descriptive research method with a qualitative approach. Results: The findings in this study are that there are many deficiencies in terms of both content of policy and policy implementation. Limitations: this research only analyzes the implementation of Local Government In Waste Management (Distrito) Dili City, Timor Leste. Contribution: This research becomes scientific information for public administration science. Keywords: Waste management, Content of policy, Policy implementation